Screening of connexin 26 in nonsyndromic hearing loss - Moreira, Danielle [UNESP]; Silva, Daniela Da [UNESP]; Lopez, Priscila [UNESP]; Mantovani, Jair Cortez [UNESP] (Thieme, 2013)
Introduction The first locus for nonsyndromic autosomal recessive hearing loss is on chromosome 13q11-22. The 35delG mutation is present in 80% of cases in which GJB2 is involved, which makes the study of this mutation very important. The viability and benefits of screening for mutations in the connexin 26 gene are now beginning to change the diagnostic evaluation and identification of the etiology of hearing loss. Objective To investigate the occurrence of the 35delG mutation in patients with nonsyndromic sensorineural hearing loss and their first degree relatives. Methods This transversal study included 72 patients from the local hospital. The patients were divided into three groups: group A, sensorineural hearing loss (n-=-58); group B, first-degree relatives of group A with sensorineural hearing loss (n-=-09); and group C, first-degree relatives of patients from group A without hearing loss (n-=-05). All patients had audiological evaluation and genetic testing of the 35delG mutation. Results The 35delG mutation was found in four heterozygous mutations (three of them found in the same family). The other heterozygous mutation was found in a female patient with bilateral, moderate, prelingual, sensorineural hearing loss. A single homozygous mutation was found in a male patient, with severe sensorineural hearing loss in his right ear and profound hearing loss in the left ear. Conclusions The 35delG mutation was found in 7% of the cases. The test is easy to perform and inexpensive, but it is necessary to investigate other genes related to hearing loss.
Keywords: acoustic stimulation; genetics; hearing loss